Evaluation of the Results of Introduction Work on the Example of Rare Species Allium Giganteum Regel, A. Isakulii R. M. Fritsch and F. O. Khass (Global Journal of Science Frontier Research, 2020)
The terminology used in assessing the results of introduction works has been clarified. Criteria have been developed for assessing acclimatization and adaptation. An adaptation assessment was carried out for Allium giganteum Regel, A. isakulii R. M.
Keywords: introduction; adaptation; acclimatization; allium giganteum; a isakulii